2012
DOI: 10.1007/s00402-012-1615-3
|View full text |Cite
|
Sign up to set email alerts
|

Screw length in the guided growth method

Abstract: The 8-plate has shown to be more efficient in producing angular deformity than staples. However, the length of the screw has showed no role in the 8-plate function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Several studies have tried to determine whether rigid or modular implants are more efficient at producing deformity in animal studies 13,14,16,17 or in correcting deformity in human retrospective studies. 15,18 Human studies where deformity is corrected are impossible to completely compare the benefit of each implant as a result of differences in growth plate disease, magnitude of deformity, body habitus, and differences in individual growth rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have tried to determine whether rigid or modular implants are more efficient at producing deformity in animal studies 13,14,16,17 or in correcting deformity in human retrospective studies. 15,18 Human studies where deformity is corrected are impossible to completely compare the benefit of each implant as a result of differences in growth plate disease, magnitude of deformity, body habitus, and differences in individual growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Human studies would be ideal for comparison, yet no prospective trials could be possible as it would be difficult to control for variables such as individual patient growth rates; variations in limb deformity (location and magnitude); the disease process that caused deformity; and differences in surgical methodology. Studies in smaller animals usually evaluate the deformity produced in only 1 plane and fail to account for the fact that guided growth produces a deformity that may not be fully characterized by a single radiograph.…”
mentioning
confidence: 99%
“…A sham group was not used, as in previous studies of hemiepiphysiodesis no influence had been revealed. 18,20 The surgery comprised a medial proximal tibial hemiepiphysiodesis using a twohole titanium plate and screws (Normed, Tuttlingen, Germany). The device was left in place for three weeks and then removed.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there has only been one report evaluating screw size [9] and there have been no reports on plate size or screw configuration. In this situation, it is important to obtain the maximum possible correction in the shortest amount of time.…”
Section: Discussionmentioning
confidence: 99%